Cell‐to‐cell transmission of HIV‐1 from provirus‐activated cells to resting naïve and memory human primary CD4 T cells is highly efficient and requires CD4 and F‐actin but not chemokine receptors. Issue 11 (23rd July 2022) - Lan, Jie; Li, Wei; Yu, Richard; Syed, Fahim; Yu, Qigui
Abstract: Latently infected cells harboring replication‐competent proviruses represent a major barrier to HIV‐1 cure. One major effort to purge these cells has focused on developing the "shock and kill" approach for forcing provirus reactivation to induce cell killing by viral cytopathic effects, host immune responses, or both. We conducted kinetic and mechanistic studies of HIV‐1 protein expression, virion production, and cell‐to‐cell virus transmission during provirus reactivation. Provirus‐activated ACH‐2 cells stimulated with romidepsin (RMD) or PMA produced Nef early, and then Env and Gag in parallel with the appearance of virions. Env on the surface of provirus‐activated cells and cellular F‐actin were critical in the formation of virological synapses to mediate cell‐to‐cell transmission of HIV‐1 from provirus‐activated cells to uninfected cells. This HIV‐1 cell‐to‐cell transmission was substantially more efficient than transmission seen via cell‐free virus spread and required F‐actin remodeling and CD4, but not chemokine receptors. Resting human primary CD4 + T cells including naïve and memory subpopulations and, especially the memory CD4 + T cells, were highly susceptible to HIV‐1 infection via cell‐to‐cell transmission. Cell‐to‐cell transmission of HIV‐1 from provirus‐activated cells was profoundly decreased by protease inhibitors (PIs) and neutralizing antibodies (nAbs) that recognize the CD4‐binding site (CD4bs) such as VRC01, but not by reverse transcriptase (RT) inhibitor Emtricitabine (FTC). Therefore, our results suggest that PIs with potent blocking abilities should be used in clinical application of the "shock and kill" approach, most likely in combination with CD4bs nAbs, to prevent new HIV‐1 infections. Importance: HIV‐1 eradication from infected individuals remains a major medical challenge. Combination antiretroviral therapy (ART) has led to a profound reduction in HIV‐1‐related morbidity and mortality. However, ART fails to eliminate HIV‐1, as patients on ART still have residual viremia. The persistent viremia mainly arises from replication‐competent proviruses in long‐lived latently infected cells, which represent a major obstacle for HIV‐1 eradication. One major effort to purge these latently infected cells has focused on developing the "shock and kill" approach for forcing provirus reactivation to induce cell killing. The "shock and kill" approach must be used with ART to prevent new infections. We studied the kinetic and mechanistic events of HIV‐1 protein expression, virion production, and virus transmission and blockade during provirus reactivation. Our results suggest that ART regimens in clinical application of the "shock and kill" approach should contain PIs plus RT inhibitors to simultaneously prevent and inhibit new infection from provirus‐activated cells.